Association Analysis of a Regulatory Variation of the Serotonin Transporter Gene with Severe Alcohol Dependence - Sander, Thomas; Harms, Helmut; Lesch, Klaus-Peter; Dufeu, Peter; Kuhn, Silke; Hoehe, Margret; Rommelspacher, Hans; Schmidt, Lutz G. (Alcoholism, clinical and experimental research, 1997)
The present study tested the hypothesis that the short, low activity variant of a biallelic polymorphism in the 5’regulatory region of the human serotonin transporter (5‐HTT) gene confers susceptibility to severe alcohol dependence marked by severe withdrawal symptoms. Applying a phenotype‐genotype strategy, our population‐based association analysis included 216 German controls and an extreme sample of 103 severely affected alcoholics who were selected from 315 German alcohol‐dependent subjects by a history of alcohol withdrawal seizure or delirium. The frequency of the short allele (S) was significantly increased in the severely affected alcoholics, compared with that in the controls (X2= 3.87, df= 1, nominal p= 0.049). The post‐hoc exploration indicated that this allelic association resulted exclusively from a significant excess of the S/S genotype in the severely affected alcoholics (p= 0.035), suggesting a recessively acting effect. Consistently, we found a weak but significant correlation (p= 0.013) between the frequency of the S/S genotype and severity of withdrawal symptoms (WDS): no WOS [18.3%, odds ratio (OR) = 1.16], vegetative WDS only (21.8%, OR = 1.44), and severe WDS with either withdrawal seizure only or delirium only (25.0%, OR = 1.69), and both withdrawal seizure and delirium (30.8%, OR = 2.30). Further studies are required to test whether the tentative genotype‐phenotype relationship occurred by chance or reflects a real genotypic association between a recessively modifying effect of the short variant of the functional 5‐HTT promoter polymorphism and alcohol withdrawal vulnerability.